Merumuskan Tujuan dan Manfaat Penelitian - Syafruddin Jamal (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2012)
Technically in research, the problem can be defined as a question about the relationship between two or more variables that explain a phenomenon. The relationship between these variables can be: correlation, differences, influences. Then, the research goals set to get clearer answers and strengthen the previous explanation of the formulation of research problems. The significance of research to get the answers and description from the research, and the benefits can be taken from the research.